Optimasi Sifat Reologi Lumpur KCl-Polymer Polyamine pada Suhu 300°F dengan Menggunakan XCD Polymer - Ramadhan, Rusandy; Rafsanzani, Fachri Insani; Rahman, Muhammad Rizqie Fathan; Sitompul, Maria Sinka Elizabeth (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The drilling fluid system is a crucial component in drilling operations. Problems commonly occur when penetrating formations containing reactive clay or shale, which may affect wellbore stability. Drilling fluid functions to maintain wellbore conditions; therefore, chemical additives are required to improve mud properties. This study aims to evaluate the mud properties of Water-Based Mud of the KCl Polymer Polyamine type through testing at original temperature, 200°F, 250°F, and 300°F. The measured parameters include mud weight, pH, rheology, API filtrate, solid content, MBT, K+, and Cl-. At 300°F, the rheological values did not meet the specification, requiring additional XCD Polymer of 0.1–0.4 ppb. The results indicate that adding 0.3 ppb XCD Polymer produces suitable rheological properties at high temperature. Mud preparation was performed by mixing and testing using mud balance, rheometer, API filtrate press, retort kit, and digital pH meter with Bentonite, NaOH, Starch, PAC-LV, Soltex, CaCO3, XCD, Barite, KCl-Polymer, and Polyamine.